Penerapan Konsep Kearifan Lokal Masyarakat Sunda (Sabilulungan) dalam Pembelajaran Sejarah - Sutarman, Usep (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2017)
About 1400 years ago, the Prophet Muhammad saw states that the main mission in educate people is to making perfect akhlak and trying to build good characters. It is so important about akhlak and character of human beings from the Prophet Muhammad saw that he gives good examples in educating his peoples. As well as these days, human’s akhlak and self existence is very important to see, grow so that someone’s/student’s potential can grow and finally becomes the character. A nation will be strong if the citizens have the sense of self-existences of his nation. The sense of self-existence will be planted well if the citizens have the horizon of the history journey of his nation. The planning of the sense of self-existence of his nation can be done in the very strategic activities which is through the history learning in the school which indeed the full of the active, innovative and fun history learning and full with the precious heritages.